From Devolution to Private Enterprise: The Dynamics of Ecotourism Governance in Gunung Halimun National Park - Kusumastuti, Gayatri; Shohibuddin, Mohamad (Indonesian Journal of Tourism and Leisure, 2025)
This article examines changes of governance regime in the Curug Nangka ecotourism area, Bogor. Initially a production forest managed by Perum Perhutani (state-owned company), it later became a conservation forest under the management of the Gunung Halimun Salak National Park Agency, and is now managed by a private company. These shifts in governance regimes have significantly impacted community involvement in managing the ecotourism area. A survey of 32 respondents, supported by in-depth interviews, revealed that Perhutani’s governance regime scored highest in legitimacy, voice, strategic vision, and equity indicators, followed by the National Park Agency, with the private company ranking lowest. However, the private company performs better management and revenue-sharing with local communities and village authorities. As a result, in terms of performance and accountability indicators, most respondents ranked the private company higher than the other two regimes. By comparing these three governance regimes, this article contributes to identifying key aspects in the governance of ecotourism area that ensure community participation and explores community responses to these changes of governance regime.